Academic Self-Efficacy and Mental Well-Being of Unprivileged Senior High School Students - Quesea, Ethel; Azana, Bernard; Combalicer, Christian Reynold; Romero, Kay Ann (12th International Scholars Conference 2025, 2026)
This study sought to investigate the impact of academic self-efficacy on the mental well-being of underprivileged senior high school students, specifically 4Ps beneficiaries at Burdeos National High School in the Philippines. Based on Albert Bandura’s Self-Efficacy Theory and Yoesoep Edhie Rachmad’s Mental Well-being Theory, the research examined the correlation between students' confidence in their academic ability and their emotional, social, andfunctional well-being. The study utilized a quantitative, descriptive-correlational research approach to survey 288senior high school pupils. Descriptive analysis indicated that students exhibited high academic self-efficacy (M = 4.21, SD = 0.56) and excellent mental well-being, notably in positive emotions and thinking, relationship andfunctioning. Correlational analysis revealed a moderate positive correlation between academic self-efficacy andmental well-being (r = 0.43, p = 0.000). However, regression analysis indicated that academic self-efficacy (β = 0.213, p = 0.215), sex (β = 0.021, p = 0.833), and age (β = 0.093, p = 0.341) were not statistically significant predictors of mental well-being. These data substantiate theoretical assertions that self-efficacy influences psychological functioning, while also emphasizing the intricacy of mental well-being. The research provides significant insights for educators, counselors, and legislators in formulating tailored assistance for disadvantaged adolescents. It emphasizes the significance of cultivating academic confidence and mental well-being, acknowledging that supplementary social and environmental aspects must be considered to promote comprehensive student development.